1983
DOI: 10.3189/s0022143000030380
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Shear Frames

Abstract: ABSTRACT. The shear frame is a simple in situ device for indexing the s hear strength of thin weak layers. The index is sensitive to shear-frame geom etry, rate-of-pull , and shear-frame ma ss. It is time-consuming to carefu ll y align the device on the Gleitschicht (shear failure plane) in a slab avalanche zone. The ratio shea r fra me index/ shear stress of the Gleitschicht has a high va rian ce, a nd may not be a fundamental mea s ure of slab avalanche sta bility. Corrections for th e normal stress on the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 4 publications
3
32
1
Order By: Relevance
“…This observation is similar to that of Perla and Beck [1983], who observed that higher pull rates on a shear frame lowered shear strength values by 25%. Perla and Beck [1983] also noted that shear strength measurements were affected by the normal load applied to the frame. The only way to improve accuracy has been to increase the number of measurements while using a rotation speed as constant as possible, about 1 s for a 180°rotation, which we consider fast.…”
Section: Instrumentationsupporting
confidence: 90%
“…This observation is similar to that of Perla and Beck [1983], who observed that higher pull rates on a shear frame lowered shear strength values by 25%. Perla and Beck [1983] also noted that shear strength measurements were affected by the normal load applied to the frame. The only way to improve accuracy has been to increase the number of measurements while using a rotation speed as constant as possible, about 1 s for a 180°rotation, which we consider fast.…”
Section: Instrumentationsupporting
confidence: 90%
“…The observation of increase in the shear strength with applied compressive pressure is in agreement with different studies (Gaume et al, 2014;Perla and Beck, 1983;Zeidler and Jamieson, 2006). In all these studies the shear strength of snow is found to be increasing up to a certain value of applied compressive pressure.…”
Section: Resultssupporting
confidence: 87%
“…FCsf (Chandel et al 2014b , 10 Feb 2010 e. FCsf (Chandel et al 2014b , 19 Feb 2010 f. Cohesive Snow (Perla and Beck, 1983) g.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the first 24 hours some 0.5 mm facets formed where the dry snow lay on the freezing wet layer. Also, the shear strength measured with a shear frame [see, e.g., Perla and Beck , 1983; Sommerfeld , 1984] dropped 50%. This decrease was attributed partly to a shear stress concentration resulting from the freezing and stiffening of the wet layer and partly to the formation of facets at the interface.…”
Section: Formation Of Facets Near Crustsmentioning
confidence: 99%